KAPASITAS ASIMILASI TOTAL SUSPENDED SOLID (TSS) DI MUARA SUNGAI NERBIT BESAR KELURAHAN LUBUK GAUNG KECAMATAN SUNGAI SEMBILAN KOTA DUMAI PROVINSI RIAU - Romel Kefriansa Putra; Rifardi '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the ability of estuary to accommodate the total suspended solids that was derived from household activities, or other events and factors at Nerbit Besar River of Lubuk Gaung Village of Sungai Sembilan Sub-District of Dumai City Riau Province. The results showed that the volume of the estuary during spring tide (Vh) was bigger than the volume of the estuary at low ebb tide (VI). The pollution load into the estuary of Nerbit River at ebb tide was bigger than when spring tide. Estuary volume in high at tide (Vh) was bigger than the volume of the estuary at during neap tide (VI). The pollution load into the estuary of Nerbit River during ebb tide was bigger than neap tide. Conditions assimilation capacity at the spring tide and during neap condition has not been exceeded (under capacity) because the value of the load capacity (KB) (KBS, KBP, and KBBM) bigger (BP) pollutant load.Kata Kunci: Assimilation Capacity, Total Suspended Solid (TSS), Nerbit Besar River